2014
DOI: 10.2147/bctt.s46020
|View full text |Cite
|
Sign up to set email alerts
|

Candidate prognostic markers in breast cancer: focus on extracellular proteases and their inhibitors

Abstract: The extracellular matrix (ECM) is the complex network of proteins that surrounds cells in multicellular organisms. Due to its diverse nature and composition, the ECM has a multifaceted role in both normal tissue homeostasis and pathophysiology. It provides structural support, segregates tissues from one another, and regulates intercellular communication. Furthermore, the ECM sequesters a wide range of growth factors and cytokines that may be released upon specific and well-coordinated cues. Regulation of the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 111 publications
0
24
0
Order By: Relevance
“…fibronectin) and proteoglycans (e.g. chondroitin sulfate) [64]. While initially regarded as a stable structure solely providing support, newer studies indicate that the ECM is surprisingly dynamic and versatile, and represents a key player in cellular processes such as cell growth, proliferation and migration [64,65].…”
Section: Components Of the Microenvironment And Their Interplay With mentioning
confidence: 99%
See 3 more Smart Citations
“…fibronectin) and proteoglycans (e.g. chondroitin sulfate) [64]. While initially regarded as a stable structure solely providing support, newer studies indicate that the ECM is surprisingly dynamic and versatile, and represents a key player in cellular processes such as cell growth, proliferation and migration [64,65].…”
Section: Components Of the Microenvironment And Their Interplay With mentioning
confidence: 99%
“…chondroitin sulfate) [64]. While initially regarded as a stable structure solely providing support, newer studies indicate that the ECM is surprisingly dynamic and versatile, and represents a key player in cellular processes such as cell growth, proliferation and migration [64,65]. The ECM is often disorganized and deregulated in cancer, leading to abnormal behavior of cells through feedback regulatory mechanisms [65].…”
Section: Components Of the Microenvironment And Their Interplay With mentioning
confidence: 99%
See 2 more Smart Citations
“…At the level of transcription, analyses of large microarray patient datasets have identified MMP-1, -9, -12, -14, and -15 as predictive of adverse outcome in one dataset comprised of primary tumors from 295 patients (33, 34), and MMP-9, -11, and -15 as associated with poor survival in another dataset of primary tumors from 1500 patients (35, 36). Neither of these studies identified associations of any MMPs with positive outcomes.…”
Section: Mmps In Breast Cancer and Their Clinical Significancementioning
confidence: 99%